Reconstructing Legal Protections for Justice Collaborators within the Criminal Justice System as an Effort to Uncover Common Crimes in Indonesia - Indriawati, Sri Endah; Prastiwi, Dian Eka; Tuanaya, Halimah Humayrah (Sinergi International Journal of Law, 2023)
Perpetrators of general crimes who are willing to cooperate with law enforcement are commonly referred to as justice collaborators. These individuals play a crucial role as a valuable source of information for law enforcement agencies in unveiling general crimes, particularly those involving intricate criminal networks. Justice collaborators offer testimony, guidance, and even assist in securing substantial evidence to bolster criminal cases currently under investigation by authorities. The primary objective of this research is to examine the overhaul of legal safeguards for justice collaborators within the Indonesian criminal justice system, aiming to facilitate the detection of general criminal activities. This research adopts a normative legal research approach with a statutory focus. The author, in addressing the research question, relies on primary legal sources, secondary legal materials, and tertiary legal references as parameters for problem resolution. For data collection, a qualitative approach was chosen, specifically emphasizing a quality assessment. Consequently, the technique employed for data collection in this study is qualitative analysis. Within this research, two pivotal issues related to reconstruction will be elucidated. First, the study will delve into the prerequisites for conferring justice collaborator status in general crimes. Second, it will explore the reconstruction of general criminal acts as actions eligible for justice collaborator involvement.